Does contextual learning matter in fire hazard recognition awareness campaigns? - Faiz, Tauqeer; Tee, Mark Kit Tsun; Al Mahmud, Abdullah (Frontiers in Virtual Reality, 2025)
BackgroundUrban residents are facing increasing levels of exposure to extreme conditions, driven by global warming, urbanization, and the abundance of combustible materials in heavily constructed environments. There is an urgent need for evidence-based, innovation-driven public safety awareness. Frequent fire incidents in the Emirates of Sharjah and Dubai highlight the glaring deficiencies in conventional awareness safety campaigns.ObjectiveThis study aimed to enhance fire hazard recognition skills among residents, enabling them to recall and apply fire safety guidelines in their homes or apartments within a contextual, engaging, motivating, and immersive learning environment.MethodsTwo virtual reality-based environments were developed and evaluated. The first virtual reality platform provided fire safety content in a non-contextual form based on available awareness campaign materials such as brochures, leaflets, and videos. The second virtual reality platform offered contextual simulations that mimicked realistic apartment and home fire hazard scenarios. A pre-test/post-test experimental design was employed, and data were analyzed using paired and unequal variances t-tests to evaluate learning outcomes and usability.ResultsParticipants using the contextual virtual reality platform demonstrated significantly higher improvements in fire hazard identification skills than those using the non-contextual platform. The contextual group also showed higher engagement and perceived usefulness. Usability testing conducted using the System Usability Scale confirmed the superior performance of the contextual model, which achieved the highest mean score among the evaluated options.DiscussionContextual, immersive learning environments significantly outperformed traditional materials in promoting hazard awareness skills. This study supports the use of scenario-based virtual reality training as an effective tool for public safety education, particularly in high-risk and urban areas where traditional campaigns may be ineffective.